Mindful Learning: A Case Study of Langerian Mindfulness in Schools - Davenport, Chase; Pagnini, Francesco (Frontiers in Psychology, 2016)
The K-12 classroom applications of mindfulness as developed by Ellen Langer are discussed in a case study of a first-year charter school. Langerian Mindfulness, which is the act of drawing distinctions and noticing novelty, is deeply related to well-being and creativity, yet its impact has yet to be tested at the primary or secondary school level. The objective of the article is to display how Langerian Mindfulness strategies could increase 21st century skills and Social-Emotional Learning in primary classrooms. The New School San Francisco, an inquiry-based, socioeconomically and racially integrated charter school, serves as a model for mindful teaching and learning strategies. It is concluded that when mindful strategies are implemented, students have significant opportunities to exercise the 21st century skills of creativity, collaboration, communication and critical thinking. Langerian Mindfulness is also considered as a tool for increasing Social-Emotional Learning in integrated classrooms. It is recommended that mindful interventions be further investigated in the primary and secondary school context.